Association of two novel adiposity indicators with visceral fat area in type 2 diabetic patients: Novel adiposity indexes for type 2 diabetes. Issue 19 (May 2020) - Liu, Junru; Fan, Dongmei; Wang, Xing; Yin, Fuzai
Abstract : Abstract: The present study evaluated the performance of 2 novel adiposity indicators, body shape index (ABSI), and body roundness index (BRI), to determine the accumulation of visceral fat in type 2 diabetic patients. A cross-sectional study was performed on 233 type 2 diabetic patients from Qinhuangdao, China. Visceral fat area (VFA) was measured using bioelectrical impedance. Accumulation of visceral fat was defined as VFA ≥ 100 cm 2 . In diabetic males, the area under the curve (AUC) values were 0.904 for waist circumference (WC), 0.923 for BRI, and 0.788 for ABSI. In diabetic females, the AUC values were 0.894 for WC, 0.915 for BRI, and 0.668 for ABSI. The AUCs were similar between BRI and WC ( P > .05). The AUC for ABSI was lower compared to WC and BRI ( P < .05). The optimal cut-off for BRI was 4.25 for diabetic males (sensitivity = 87.8% and specificity = 81.1%) and 4.75 for diabetic females (sensitivity = 80.8% and specificity = 88.1%). BRI was an effective indicator for determining the accumulation of visceral fat in type 2 diabetic patients, however, it was not better compared to WC.